2021
DOI: 10.1016/j.brs.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the optimal pulse number and frequency for inducing analgesic effects with motor cortex rTMS

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Although the motor cortex is predominantly involved in mo-tor control, it is also responsible for somatosensation via its anatomical and functional connections with somatosensory cortices and the thalamus [19]. In fact, motor cortex rTMS has a clear impact on the transmission of sensory information from the body parts [20][21][22]. This argument is also consistent with findings that motor recovery following stroke is positively associated with sensory functioning [2].…”
Section: Introductionsupporting
confidence: 78%
“…Although the motor cortex is predominantly involved in mo-tor control, it is also responsible for somatosensation via its anatomical and functional connections with somatosensory cortices and the thalamus [19]. In fact, motor cortex rTMS has a clear impact on the transmission of sensory information from the body parts [20][21][22]. This argument is also consistent with findings that motor recovery following stroke is positively associated with sensory functioning [2].…”
Section: Introductionsupporting
confidence: 78%
“…Even if the neuroanatomical target is correct, the parameter space for TMS is large and not fully understood. For example, one study showed that 10Hz rTMS with 1,500 pulses induced analgesic effects, but 10 and 20Hz stimulation with 3,000 pulses had no effect 57 . The ideal parameters and protocols for improving CPSP require significant work and testing in randomized–controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that 10Hz rTMS with 1,500 pulses induced analgesic effects, but 10 and 20Hz stimulation with 3,000 pulses had no effect. 57 The ideal parameters and protocols for improving CPSP require significant work and testing in randomized-controlled trials. Lastly, per convention in the pain literature, 35,36 we used a binary cutoff to classify patients as "responders" or "nonresponders."…”
Section: Limitationsmentioning
confidence: 99%
“…Transcranial Magnetic Stimulation (TMS) is a safe and non-invasive form of brain stimulation which provides a window to investigate the causal role of brain activations in psychological processes. Theta-burst stimulation (TBS) is one of the most established repetitive TMS protocols and has the capacity to modulate neural excitability and connectivity ( Che, Cash, et al, 2021 ; Che et al, 2021 ; Huang et al, 2005 ; Ni et al, 2014 ). Specifically, intermittent TBS (iTBS) is designed to increase cortical excitability with a burst mode ( Huang et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%